Biofortifying multiple micronutrients and decreasing arsenic accumulation in rice grain simultaneously by expressing a mutant allele of OAS-TL gene - Xu, Xuejie; Sun, Shengkai; Gao, Axiang; Huang, Xin-Yuan; Wirtz, Markus; Hell, Rüdiger; Zhao, Fang-Jie (The new phytologist, 2024)
Rice grains typically contain relatively high levels of toxic arsenic (As) but low levels of essential micronutrients. Biofortification of essential micronutrients while decreasing As accumulation in rice would benefit human nutrition and health. We generated transgenic rice expressing a gain-of-function mutant allele astol1 driven by the OsGPX1 promoter. astol1 encodes a plastid-localized O-acetylserine (thiol) lyase (OAS-TL) with Ser189Asn substitution (OsASTOL1S189N), which enhances cysteine biosynthesis by forming an indissociable cysteine synthase complex with its partner serine acetyltransferase (SAT). The effects on growth, As tolerance, and nutrient and As accumulation in rice grain were evaluated in hydroponic, pot and field experiments. The expression of OsASTOL1S189N in pOsGPX1::astol1 transgenic lines enhanced SAT activity, sulphate uptake, biosynthesis of cysteine, glutathione, phytochelatins and nicotianamine, and enhanced tolerance to As. The expression of OsASTOL1S189N decreased As accumulation while increased the accumulation of multiple macronutrients (especially sulphur, nitrogen and potassium) and micronutrients (especially zinc and selenium) in rice grain in a pot experiment and two field experiments, and had little effect on plant growth and grain yield. Our study provides a new strategy to genetically engineer rice to biofortify multiple essential nutrients, reducing As accumulation in rice grain and enhancing As tolerance simultaneously.